Atmospheric pressure glow discharge plasma polymerization for surface treatment on sized basalt fiber/polylactic acid composites - Kurniawan, Denni; Kim, B.; Lee, H.; Lim, J. (Elsevier, 2012)
This study evaluates the effects of atmospheric pressure glow discharge plasma polymerization on basalt fiber to the properties of basalt fiber/polylactic acid composite. Plasma exposure time was the object of interest so the basalt fiber was exposed to the glow for 0.5, 1.5, 3, 4.5, and 6 min, respectively. Characterization was conducted on the plasma polymerized fibers by identifying the molecular bonds and surface morphology. Properties (mechanical and thermal) and water absorption behavior of the fabricated composites were tested. Plasma exposure time on BF affected mechanical properties of its BF/PLA composite, showing a decline in mechanical properties until the BF was plasma polymerized beyond 1.5 min. Optimum plasma polymerization on BF was for 4.5 min of plasma exposure time where the composite's strength and modulus were 45% and 18% higher, respectively, compared to those of untreated one. © 2011 Elsevier Ltd. All rights reserved.